8-(N,N-diethylamino)-n-octyl-3,4,5-trimethoxybenzoate actions on calcium dynamics in cultured vascular smooth muscle cells. - Liu Shirley X L; Chiou George C Y; Chen Zhou (Acta Pharmacologica Sinica, 2016)
AIM: To study 8-(N,N-Diethylamino)n-octyl-3,4,5-trimethoxybenzoate (TMB), a potent Ca(2+)-antagonist, actions on cellular calcium dynamics in vascular smooth muscle cell (VSMC) cultures. METHODS: A7r5 VSMC were cultured with Fura-2 measurements of intracellular Ca2+ concentration, [Ca2+]i. RESULTS: TMB reduced [Ca2+]i from control levels and blocked [Ca2+]i increase caused by norepinephrine (NE) and 2,5-di (t-butyl)-1,4-benzohydroquinone (BHQ). [Ca2+]i reduction by TMB was further enhanced by ryanodine. CONCLUSION: TMB is an effective agent for blocking the [Ca2+]i increase caused by NE and BHQ and for enhancing the [Ca2+]i reduction caused by ryanodine.